A trend study of the media pulse incorporated survey of the AM stations ratings in Iloilo City from the year 1986-1990. - Salazar, Ruby Ann M.
This study is conducted to find out the highest ranking AM Station in Iloilo City from the year 1986 to the year 1990., Results of the survey made by Media Pulse Incorporated in Iloilo City was used in this study. In the analysis of data, ranking was used. The data showed that DYFM is the leading AM Station in Iloilo City for the last five years. However, it was found out that DYFM became the number 1 station in Iloilo City not because all of its programmes were number 1 but because almost all of its progammes were number 1. The other programmes which have lower rank were compensated when totalled thus, becoming the number 1 station in Iloilo City.